Analysis of the association between Procalcitonin and mortality by sepsis in children under 18 years of age in an intensive care unit in Pasto, Colombia between 2012 and 2014 - Pantoja-Chamorro, Freddy; Mazzillo-Vega, Liliana; Palacios-Barahona, Uriel (Universidad y Salud, 2018)
Introduction: Procalcitonin increases early in patients with sepsis; however, it is necessary to deepen the relationship between their levels and the multi-organ commitment, as well as their outcomes such as death. Objective: To determine whether there is an association between the values of Procalcitonin and death in children with sepsis entering the pediatric intensive care unit (PICU). Materials and methods: A cross-sectional study was made with patients under 18 years of age with sepsis, who entered the PICU of Los Angeles children's Hospital in Pasto, Colombia during 2012 and 2014. The relationship between the risk of death and the levels of Procalcitonin controlled by clinical and demographic covariates was analyzed. Results: Data from 325 patients with sepsis was analyzed. The disease showed a prevalence of 27.3%, from which 23.7% (77) died. The median age was 22 months, interquartile-RI range (6-84). The median Procalcitonin was 10 ng/mL, RI (2.95-38). Children with values > 10ng/mL have an increase in the risk of death from 2 to 6 times more, compared to those who presented lower values. Conclusion: Procalcitonin can be used as an indicator and predictor of the risk of death in children under 18 with sepsis.